Inclusão digital: historia de três professoras da rede pública estadual de São Paulo - Santos, Nídia Lima Queiroz dos (2009)
This work is based on recognition of the importance of the new technologies of communication and information, especially the computer, incorporated in school education as educational tool. In view of this most important aspect in teacher education, the research aimed to describe and analyze the professional development of three teachers of mathematics, from the moment they chose to include the technology in their teaching practice. The research aimed to understand the relationship of the teachers - who felt excluded digitally - with new technologies. To understand the new technologies, especially the computer, and work with them were required workshops we call "computer shops": For 7 months there were 12 encounters with specific objectives and characteristics for each, to include participants digitally. Data analysis was made from the meetings, all written and filmed - after authorization of the participants involved in the research project - with the use of technological tools, such as digital camera and MP3. After the digital inclusion of the teachers involved, trying to link the work and teaching educational tool - in our case, the computer. In this search, we met some mathematical programs, especially the Graphmatica, whose features and capabilities for the development of all types of functions, especially quadratic function, we studied. After the acquisition and development of knowledge, finally our research project with activities - reported and commented through comics - involving students in the 8th grade of elementary school do1 II and grade of high school